Dynamic Characteristics and Seismic Response of Multi-Story Wooden Tower Considering the Influence of a High Stylobate - Hao Xue; Jianyang Xue; Dejun Song; Mengjie Li; Bowen Xue; Chenwei Wu; Yan Sui (Buildings)
In situ dynamic tests were conducted on Caiyunjian Tower to investigate the influence of a high stylobate on its dynamic characteristics and seismic response through time–domain and frequency–domain methods. Finite element models were developed for Caiyunjian Tower (wooden structure and platform) and the overall structure including the high stylobate. Subsequently, models were subjected to El Centro, Taft, and Lanzhou waves at varying amplitudes. The seismic response results indicate that the overall structure model exhibits a low natural vibration frequency with closely spaced modal frequencies. As the peak seismic wave acceleration increases, both models exhibit increased acceleration, displacement, and shear responses. The Caiyunjian Tower model shows greater sensitivity to the El Centro wave, whereas the overall structure model is more responsive to the Taft wave. Under seismic waves with identical peak acceleration, the overall structure model exhibits greater dynamic responses than the Caiyunjian Tower model. The high stylobate minimally affects the lower-order frequencies of the upper structure but significantly influences the higher-order frequencies. Therefore, the high stylobate has an adverse influence on the seismic behavior of Caiyunjian Tower.